REAKSI HARGA SAHAM PERUSAHAAN AGRIBISNIS INDEKS LQ-45 TERHADAP PERUBAHAN VARIABEL MAKROEKONOMI - Alghif Aruni Nur Rukman; Harianto Harianto; Suprehatin Suprehatin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2019)
This study aims to analyze the effect of changes in macroeconomic variables, namely exchange rates, interest rates, and inflation on stock prices of agribusiness companies on the LQ-45 index. This study used monthly time series data from 2008-2018 and analyzed by the VECM method. The results showed that the stock price reaction of eight agribusiness companies in the LQ-45 index varies with changes in macroeconomic variables both in the short and long term. In the short term, changes in exchange rates had a positive and significant effect on one company stock prices, while changes in inflation and interest rates had a negative and significant effect on four companies and one company respectively. In the long term, the results showed that changes in exchange rates had a positive and significant effect on two companies’ stock prices, while it had a negative and significant effect on five companies. The result also showed that changes in inflation had a positive and negative effect on one company and six companies respectively in the long term. Also besides changes in interest rates had a positive and negative effect on two companies’ stock prices respectively.